Cloning and sequencing of LlaDCHI [corrected] restriction/modification genes from Lactococcus lactis and relatedness of this system to the Streptococcus pneumoniae DpnII system. - Moineau, S (1995)
The natural 7.8-kb plasmid pSRQ700 was isolated from Lactococcus lactis subsp. cremoris DCH-4. It encodes a restriction/modification system named LlaDCHI [corrected]. When introduced into a phage-sensitive L. lactis strain, pSRQ700 confers strong phage resistance against the three most common lactococcal phage species, namely, 936, c2, and P335. The LlaDCHI [corrected] endonuclease was purified and found to cleave the palindromic sequence 5'-GATC-3'. It is an isoschizomer of Streptococcus pneumoniae DpnII. The plasmid pSRQ700 was mapped, and the genetic organization of LlaDCHI [corrected] was localized. Cloning and sequencing of the entire LlaDCHI [corrected] system allowed the identification of three open reading frames. The three genes (llaIIA, llaIIB, and llaIIC) overlapped and are under one putative promoter. A putative terminator was found at the end of llaIIC. The genes llaIIA and llaIIB coded for m6A methyltransferases, and llaIIC coded for an endonuclease. The LlaDCHI [corrected] system shares strong genetic similarities with the DpnII system. The deduced amino acid sequence of M.LlaIIA was 75% identical with that of M.DpnII, whereas M.LlaIIB was 88% identical with M.DpnA. However, R.LlalII shared only 31% identity with R.DpnII.